Cellulose nanowhisker modulated 3D hierarchical conductive structure of carbon black/natural rubber nanocomposites for liquid and strain sensing application. (1st March 2016) - Wu, Xiaodong; Lu, Canhui; Han, Yangyang; Zhou, Zehang; Yuan, Guiping; Zhang, Xinxing
Abstract: Conductive polymer composites with "brittle" conductive structure (i.e. low percolation threshold) are widely recognized as potential sensing materials because they may exhibit a unique stimuli-responsive change of resistance. In this work, we prepared carbon black (CB)/natural rubber (NR) nanocomposites with a unique 3D hierarchical conductive structure by incorporation of cellulose nanowhiskers via latex assembly technology. This unique conductive structure endowed the CB/NR nanocomposites with very low electrical conductivity percolation threshold (1.65 vol%), large liquid sensing capacity (4427), fast response rate (168 s), and good reproducibility. The role of the hierarchical conductive structure on the liquid sensing behavior was investigated, and the mechanism was also discussed. The potential application of this material as strain sensors was also evaluated. This study offers a universal, simple, low-cost and scalable approach for manufacturing flexible multifunctional sensing materials by modulating the microstructure of the traditional CB/NR composites using natural cellulose resources. Graphical abstract: